2014
DOI: 10.17221/7533-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing system on reproductive results in ring-necked pheasants (Phasianus colchicus L.)

Abstract: A comparative analysis of reproduction parameters and hatchability results of pheasants raised under two different housing systems (cages and aviaries) was performed. In the first system the pheasants were housed in 420 cages, 3780 from the total were females. In the second housing system, 3200 pheasant hens were placed in eight aviaries, where 50 cocks and 400 hens were kept in each. The following parameters were calculated: laying rate, the percentage of hatching, small and cracked eggs, hatchability from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Đorđevic et al (2018) summarise data reporting pheasant productivity from various studies across Europe and state that females lay 40-45 eggs, of which 85-95% are classed as fertile and of these 55-70% hatch, with 3-10% of chicks dying before the age of release. For mallard (43,677 registered as held for breeding in APHAPR2020, the breeding ratio is similar to that of pheasants (Kontecka et al 2014). Cheng et al (1980) report that mallard reared in the USA closed-flock game farms produced mean clutches of 41 eggs with a fertility of 99.5% and a hatchability of 71%.…”
Section: Estimates Based On Numbers Bred and Reared For Releasementioning
confidence: 70%
See 1 more Smart Citation
“…Đorđevic et al (2018) summarise data reporting pheasant productivity from various studies across Europe and state that females lay 40-45 eggs, of which 85-95% are classed as fertile and of these 55-70% hatch, with 3-10% of chicks dying before the age of release. For mallard (43,677 registered as held for breeding in APHAPR2020, the breeding ratio is similar to that of pheasants (Kontecka et al 2014). Cheng et al (1980) report that mallard reared in the USA closed-flock game farms produced mean clutches of 41 eggs with a fertility of 99.5% and a hatchability of 71%.…”
Section: Estimates Based On Numbers Bred and Reared For Releasementioning
confidence: 70%
“…Therefore, to estimate the numbers of birds that may be being bred for release, it is necessary to consider numbers of eggs and chicks from UK and EU origins and account for various stages of productivity and mortality according to the species of interest. For pheasants (1,023,036 registered as held for breeding in APHAPR2020, the ratio of males to females maintained by breeders varies from one male to between seven and 10 females is reported (Butler and Davis 2014;Kontecka et al 2014), so we might presume that 88-91% of the birds registered for breeding are females. Đorđevic et al (2018) summarise data reporting pheasant productivity from various studies across Europe and state that females lay 40-45 eggs, of which 85-95% are classed as fertile and of these 55-70% hatch, with 3-10% of chicks dying before the age of release.…”
Section: Estimates Based On Numbers Bred and Reared For Releasementioning
confidence: 99%
“…Several studies have been performed in order to evaluate the effect of housing systems on eggshell quality parameters including conventional cages, enriched cages, litter and free-range systems. Lower number of cracked eggs have been produced in cages (Tumova and Ebeid 2005;Holt et al 2011;Kontecka et al 2014). Different eggshell weights have been reported in literature in connection with housing systems, e.g.…”
Section: Factors Affecting Eggshell Qualitymentioning
confidence: 99%
“…According to Singh et al [105], conventional cage eggs had higher albumen heights than eggs from floor chickens. In cages, fewer cracked eggs have been produced [106,107]. Mertens et al [108] investigated the impacts of various housing systems (free-range, conventional cages, aviary and enriched cages) on eggshell quality and found that aviary eggs had the strongest shells and free-range eggs had the weakest.…”
Section: Indirect Factors Affecting Egg Components As Barriers To Ext...mentioning
confidence: 99%